PERSEPSI SISWA TERHADAP MATA PELAJARAN AGAMA HINDU DI SMAN 8 DENPASAR - Siswadi, Gede Agus (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
This study aims to explore students perceptions of Hindu Religious Education subjects at SMAN 8 Denpasar. Hindu Religious Education has an important role in shaping students' character and morals, especially in the context of learning in secondary schools. This research used a qualitative approach with a case study technique, which involved in-depth interviews and observations to collect data from Hindu students at SMAN 8 Denpasar. The research subjects were selected through purposive sampling. The results showed that students perceptions of Hindu Religious Education subjects tend to be positive, especially related to the moral and spiritual values taught. However, there are also some students who feel that religious education is not very prospective in the world of work. Factors that influence students perceptions include the teacher’s teaching methods, the influence of the social environment, and its relationship with the world of work. Based on these findings, it is suggested that the teaching of Hindu Religious Education should emphasise a more contextual and applicable approach, so that students can feel the relevance of the lessons in their lives. This research is expected to provide insights for the development of teaching methods that are more effective in increasing students' understanding and appreciation of Hindu Religious Education subjects.